The Effect of the Implementation PQ4R Strategy (Preview, Question, Read, Reflect, Recite, Review) on the Mathematical Problem-Solving Ability and Confidence of SMAN 1 Sembakung Students - Mahyudin Mahyudin; Syukrul Hamdi (International Journal of Mathematics and Science Education, 2025)
This study aims to determine the effect of the application of PQ4R (Preview, Question, Read, Reflect, Recite, Review) learning strategies on the mathematical problem-solving ability and confidence of students at SMAN 1 Sembakung, Nunukan Regency. The background of this research is the low ability of students to solve mathematical problem-solving problems and their lack of confidence in facing academic challenges. The PQ4R strategy was chosen because it is considered to be able to encourage active student engagement, build deep understanding, and strengthen confidence through structured learning steps. This study uses a quantitative method with a quasi-experimental design of the pretest-posttest control group design. The research sample consisted of 73 students in grade XI who were divided into experimental and control groups at random. The research instruments include problem-solving ability tests and confidence questionnaires. The data analysis technique used t-test and MANOVA (Hotelling's Trace) after meeting the normality and homogeneity tests. The results showed that PQ4R learning strategies had a significant effect on students' mathematical problem-solving skills and confidence. The experimental group experienced a higher score increase than the control group. Thus, the PQ4R strategy can be an effective learning alternative to improve the quality of mathematics learning as well as students' affective aspects such as confidence.